1996
DOI: 10.1080/00206819709465371
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics of the Sivas Basin: The Neogene Record of the Anatolian Accretion Along the Inner Tauric Suture

Abstract: The Sivas Basin extends over a major crustal structure underlying the contact zone between the Tauride and Pontide belts. The Kirsehir block, a continental crustal element lying between the main belts, introduces a subordinate suture in front of the Pontides-the Inner Tauride suture. The junction of the two main sutures occurs between Hafikand Imranli. Four structural zones have been considered. The northern basement of the basin, which includes both the Kirsehir continental crust and thrust sheets of ophiolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 26 publications
1
64
0
1
Order By: Relevance
“…The Sivas Basin formed from the Paleocene to the Pliocene in a foreland fold-and-thrust belt basin setting is located in the Central Anatolian Plateau, Turkey (Figure 2a) (Kurtman, 1973;Cater et al, 1991;Guezou et al, 1996;Poisson and Guezou, 1996;Gündogan et al, 2005). At the end of the Eocene, a huge accumulation of marine evaporitic deposits occurred in the Sivas Basin.…”
Section: The Inceyol Minibasin: Geologic Settingmentioning
confidence: 99%
“…The Sivas Basin formed from the Paleocene to the Pliocene in a foreland fold-and-thrust belt basin setting is located in the Central Anatolian Plateau, Turkey (Figure 2a) (Kurtman, 1973;Cater et al, 1991;Guezou et al, 1996;Poisson and Guezou, 1996;Gündogan et al, 2005). At the end of the Eocene, a huge accumulation of marine evaporitic deposits occurred in the Sivas Basin.…”
Section: The Inceyol Minibasin: Geologic Settingmentioning
confidence: 99%
“…The Sivas Basin has been interpreted as a remnant basin between the Pontides and the Tauride Platform (Kelling et al, 1989;Cater et al, 1991) or as a remnant basin resulting from Inner Tauride Ocean closure (Ş engör and Yılmaz, 1981;Koçyigit, 1990;Gökten, 1993a;Guezou et al, 1996) and/or a collisional relict of the Neo-Tethyan Ocean (Gökten, 1993b;Poisson et al, 1995Poisson et al, , 1996. Alternatively, it has also been interpreted as a postcollisional basin that formed after closure of the northern branch of Neo-Tethys (Yılmaz, 1994(Yılmaz, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…The basin is overlain by the Central Anatolian Thrust Zone. Guezou et al (1996) reported that the Sivas Backthrust is a major structure in the basin along a tectonic line extending from Imranli to Gemerek with NE-SW orientation (Figures 10 and 11). Guezou et al (1996) describes the northern region of Sivas backthrust as Kızılırmak basin, by expressing that lower Pliocene age Sivas Backthrust develops from southeast to northwest.…”
Section: Fissure Analysis Of the Kizilirmak Formationmentioning
confidence: 98%
“…Guezou et al (1996) reported that the Sivas Backthrust is a major structure in the basin along a tectonic line extending from Imranli to Gemerek with NE-SW orientation (Figures 10 and 11). Guezou et al (1996) describes the northern region of Sivas backthrust as Kızılırmak basin, by expressing that lower Pliocene age Sivas Backthrust develops from southeast to northwest. So the sediments of Kızılırmak basin on which the travertines of Sıcak Çermik, Delikkaya, Sarıkaya, Başıbüyük and Paşafabri-kası are located, have been under the effects of compressional regime in NW-SE direction since lower Pliocene and show unique deformation styles of that regime (Figure 12).…”
Section: Fissure Analysis Of the Kizilirmak Formationmentioning
confidence: 98%